Neuroprotective Effect of Lactobacillus gasseri MG4247 and Lacticaseibacillus rhamnosus MG4644 Against Oxidative Damage via NF-κB Signaling Pathway - Ji Yeon Lee; Ju Hui Kim; Jeong-Yong Park; Byoung-Kook Kim; Ho Jin Heo; Soo-Im Choi (Fermentation, 2025)
Probiotics have recently gained attention as modulators of the gut–brain axis in neurodegenerative diseases such as Alzheimer’s disease. In this study, we identified probiotic strains with neuroprotective effects and investigated their mechanisms and safety. We screened strains based on their ability to inhibit acetylcholinesterase (AChE) activity and protect cells against H2O2-induced damage. The cell-free supernatants (CFS) of Lactobacillus gasseri MG4247 and Lacticaseibacillus rhamnosus MG4644 inhibited AChE activity and reduced cell damage and reactive oxygen species generation. These effects were mediated through inhibition of the MyD88/NF-κB pathway and modulation of the JNK/Bax-dependent apoptotic pathway in neuronal cells treated with H2O2. Whole-genome sequencing and antibiotic susceptibility testing confirmed the identity and safety of both strains. These findings suggest that MG4247 and MG4644, as probiotics, may help protect neuronal cells from oxidative stress and inflammation.